Identifikasi Bakteri Coliform Pada Lalapan Kubis Yang Dijual Pedagang Pecel Lele Kaki Lima Di Sekitar Kampus Stkip Ypm Bangko - Rozana Zuhri (Pendidikan Biologi STKIP YPM Bangko, 2019)
Food is important both for growth and maintaining life vegetables have nutritional advantages because they are consumed in a raw state so that the nutrients contained in them do not experience denaturation or change. But the benefits of vegetables will not be useful if the vegetables contain E. coli bacteria that enter the digestive tract. The study is a laboratory descriptive experimental research. The study was conducted at a street , treders pecel lele found on Bangko City's Sumatra Cross Road. The number of samples in this study were 13 street treders selling pecel lele. Sample examination was carried out in the STKIP YPM Bangko Biology Education Laboratory. Data were analyzed by univariate. From the results of the study found two positive E. coli cabbage and positive Coliform in all samples of cabbage / cabbage.